The serum levels of IL-8, IL-10, and TNF-α, Cardiac troponin I (cTnI), Creatine kinase-MB (CK-MB) in Patients with Rheumatic Heart Disease Received Dexmedetomidine: serum levels of IL-8, IL-10, and TNF-α, Cardiac troponin I (cTnI), Creatine kinase-MB (CK-MB) - Zhang, Caiyun (Journal of Medical Biochemistry, 2025)
Introduction: It aimed to explore the application of dexmedetomidine (DEX) in rheumatic heart disease (RHD) valve replacement surgery and its effect on serum levels of IL-8, IL-10, and TNF-α, Cardiac troponin I (cTnI), Creatine kinase-MB (CK-MB). Material and Method: 140 cardiopulmonary bypass (CPB) heart valve replacement patients in West China Hospital Of Sichuan University between January 2022 and December 2024 were randomly grouped: observation group and controls. The observed subjects were given DEX, and the controls was given normal saline. The amount of anesthetic, the myocardial injury markers, cellular immune function, inflammatory factors, and adverse reactions were observed. Result: As against the controls, the observation group had visibly lower anesthetic dosage, higher heart rate (HR) at T5 and mean arterial pressure (MAP) at T2, T3, and T5, and lower myocardial injury markers (P < 0.05). There were similar in CD4+, CD8+, and CD4+/ CD8+ between subjects before surgery. As against the controls, CD4+ and CD4+/CD8+ were visibly higher, and CD8+was visibly lower in the observation group during and following operation (P < 0.05). There was similar in interleukin-8 (IL-8), IL-10, and tumor necrosis factor-α (TNF-α) before operation (P > 0.05). As against the controls, the postoperative IL-8 and TNF-α were visibly lower, and IL-10 was visibly higher in observed subjects (P < 0.05). There was similar in adverse reactions of the subjects (P >0.05). Conclusion: DEX can reduce the dosage of anesthetics, maintain hemodynamic stability, reduce myocardial injury, and reduce the level of inflammatory factors.